The importance of religion : meaning and action in our strange world - Flood, Gavin D., 1954- (Malden, MA : Wiley-Blackwell, 2012)
'The Importance of Religion reveals the significance of religion in modern times, showing how it provides people with meaning to their lives and helps guide them in their everyday moral choices Provides readers with a new understanding of religion, demonstrating how in its actions, texts and world views religion is enduring and vividly engages with the mystery of the world Offers striking arguments about the relationship of religion to science, art and politics Engagingly written by a highly respected scholar of religion with an international reputation'--
'In spite of the noble efforts of scientific reason to reveal everything to us, in many ways the world remains a mysterious place. For so many people, religion continues to represent a crucial guide to navigating through the strange world we all inhabit -- yet never in history has religion been more misunderstood. The Importance of Religion illuminates the central importance of religion in modern times, revealing how it crucially provides people with meaning to their lives and guides them in their everyday moral choices. Renowned religion scholar Gavin Flood argues that modern religions do not just represent passive notions about the nature of reality, but are active and inspirational -- they show us ways of living, dying, choosing a good life, and inhabiting the strange and mysterious world of the twenty-first century. In a wide-ranging, engaging and brilliant book, Gavin Flood discusses the nature and meaning of religion and spirituality; and religion's relationship with politics, science, evolutionary biology, human rights, culture, humanism, and more. The Importance of Religion offers rich insights into the myriad ways religion provides meaning to the lives of people and communities in the modern world'--
Includes bibliographical references and index.
Keywords: Religion -- Philosophy